An Operation Adjustment Method for Intercity High Speed Maglev Train - LI Xun; SHI Yangyang; PENG Qin (Kongzhi Yu Xinxi Jishu)
The intercity high speed maglev train runs automatically according to the train operation diagram / timetable issued by the central control system. Based on historical operation data and traffic flow, this paper established a framework model for operation adjustment based on optimized train operation diagram. Train collision detection method was used to check the model. Finally, the simulation software was used to verify the model, and the scientific and reasonable operation plan and adjustment model were obtained.